Characteristics of Social Relations of Youth With Antisocial Behaviour That Overuse Psychoactive Substances - Hrnčić, Jasna; Brkić, Miroslav; Žegarac, Nevenka (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
High comorbidity of antisocial behaviour and overuse of psychoactive substances (PAS has been found in numerous studies. The paper aims to establish the degree of presence of overuse (abuse or dependence) of PAS by youth with antisocial behaviour and to analyse the association between the overuse of PAS by youth with antisocial behaviour and characteristics of their social environment. Research was conducted among youth placed in educational and correctional institutions because of crime they had committed. Altogether 57.1% (n=109) of 191 subjects overused PAS. They differentiated from the youth who don’t overuse PAS in significantly lower emotional exchange and individuation in family, lower intimacy and openness in communication with mother, higher psychological control, more inefficient monitoring and less consistent disciplining by mother, reduced inner control in regard to mother’s expectations and more distinctive pro-criminal behaviour of peer group. Given characteristics were sensitive but not specific in the prediction of overuse of PAS by youth. Results were discussed in regard to findings of contemporary research.